Women’s empowerment and participation in Islamic financial planning diversity, equity and inclusion: evidence from Maqasid al-Shariah - Mohammad, Habibullah; Hassan, Rusni; Mohd. Zain, Nor Razinah (IIUM Press, 2023)
ABSTRACT: The study places a strong emphasis on its importance, given the quick changes in society that are occurring right now. Many women are pursuing various sorts of employment, including self-employment, in this era of economic liberalization and women's empowerment. However, this study aims to investigate the connection between Islam and women's empowerment by examining Maqasid al-Shari'ah perspectives on this matter. To have a thorough understanding of Islam and women's empowerment, it is imperative to consider the role played by women in the financial sector and their contribution to economic progress. Using an experiment, this study examined the relationship between confidence, gender, and race in dealing with a financial planner among various groups and races with colour and creed. The study's implications are significant for comprehending the obstacles and chances that under-represented groups encounter in pursuing financial planning success. The alignment of industry measures to raise the proportion of women and persons from varied backgrounds in the financial services sector led to the focus of this study on women and diversity. This essay examines the primary factors influencing diversity and the place of women in various financial management, CSR, and external corporate governance roles. This research also focuses on women's leadership and social diversity, focusing on female managers committed to fostering and maintaining equity and diversity inside their organizations. This study demonstrates how women plan financially for retirement based on psychological concepts and sociodemographic variables, highlighting the importance of financial management and planning for women. It showed a strong correlation between the investor's choice of investments and the strong relationship between the women's decision-making processes on the mental and financial levels. To assess the core idea of Maqasid al-Shari’ah from primary and secondary Islamic knowledge sources, which serves as a model for women's empowerment, and to pinpoint the obstacles to women's empowerment and participation in Islamic financial planning in terms of diversity, equity, and inclusion, this study employs the qualitative method.